Defining a biogeochemical baseline for sediments at Carbon Capture and Storage (CCS) sites: An example from the North Sea (Goldeneye). (March 2021) - Dale, A.W.; Sommer, S.; Lichtschlag, A.; Koopmans, D.; Haeckel, M.; Kossel, E.; Deusner, C.; Linke, P.; Scholten, J.; Wallmann, K.; van Erk, M.R.; Gros, J.; et al.
Highlights: A biogeochemical baseline of sediment geochemistry at potential offshore CCS sites. Diagnostic indicators of CO2 leakage based on stoichiometry of porewater chemistry. Porewater chemistry is modified by reverse weathering processes at Goldeneye site. Abstract: Injection of carbon dioxide (CO2 ) into subseafloor reservoirs is gaining traction as a strategy for mitigating anthropogenic CO2 emissions to the atmosphere. Yet, potential leakage, migration and dissolution of externally-supplied CO2 from such reservoirs are a cause for concern. The potential impact of CO2 leakage on the biogeochemistry of sediments and overlying waters in the North Sea was studied during a controlled subsurface CO2 release experiment in 2019 at a potential carbon capture and storage site (Goldeneye). This study describes the natural (unperturbed) biogeochemistry of sediments. They are classified as muddy sand to sandy mud with low organic carbon content (∼0.6 %). Distributions of dissolved inorganic carbon (DIC) and total alkalinity (TA) in sediment porewaters are reported in addition to in situ benthic fluxes of dissolved nutrients and oxygen between the sediments and the overlying water. Oxygen fluxes into the sediment, measured using benthic chambers and eddy covariance, were 6.18 ± 0.58 and 5.73 ± 2.03 mmol m −2 d -1, respectively. Diagnostic indicators are discussed that could be used to detect CO2 enrichment of sediments due to reservoir leakage at CCS sites. These include the ratio TA and ammonium to sulfate in sediment porewaters, benthic fluxes and chloride-normalized cation distributions. These indicators currently suggest that the organic carbon at Goldeneye has an oxidation state below zero and is mainly degraded via sulfate reduction. Carbonate precipitation is apparently negligible, whereas decreases in Mg 2+ and K + point toward ongoing alteration of lithogenic sediments by reverse weathering processes.